Improving Competitive Advantages of Higher Education Institutions through IT Governance, IT Excellence, and IT Innovation: A Case Study in School of Informatics Management & Computing in Indonesia - David David; Edi Abdurachman; Agustinus Bandur; Wibowo Kosasih (CommIT (Communication and Information Technology) Journal, 2023)
School of Informatics Management & Computing (Sekolah Tinggi Manajemen Informatika & Komputer - STMIK) in Indonesia currently needs to improve its competitive advantages, which are inseparable from capabilities to empower Information Technology (IT) for management activities. The research aims to develop IT innovation theories by studying the influences of IT governance, IT excellence, and IT innovation on the competitive advantages of STMIK in Indonesia. A sequential explanatory model is applied to collect and analyzes quantitative data in the first stage and qualitative data in the second stage. Focus Group Discussions (FGDs) method is also used to receive respondents’ statements to strengthen the research findings. The analysis unit involves private STMIK in Indonesia with heads of schools, deputies, and heads of study programs. Quantitative and qualitative research dimensions and an empirical survey, with the active participation of 85 schools, are implemented. The results emphasize that IT maturity is insignificant as a moderating variable between IT innovation and competitive advantages. Similarly, IT governance is also insignificant for the improvement of competitive advantages. However, competitive advantage is directly and favorably impacted by IT innovation initiatives. These findings demonstrate how much easier it is for universities to improve their competitive edge using their greater IT innovations. This circumstance demonstrates the enormous potential of STMIK’s IT innovation capability in Indonesia, allowing institutions to implement novel strategies to generate value by introducing new services.